Stimulation Of Early Childhood Social-Emotional Development With The Tellyng Story Method - Yubita Epifani Bobsuni; Demarti Eny; Inko Deslin Tiumate; Irma Sesfa'o; Jetri Alimia Kamlasi; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Emotional intelligence is a fundamental aspect of early childhood development because it influences children's ability to recognize and regulate emotions, demonstrate empathy, cooperate with peers, and establish positive social relationships. However, many preschool children continue to experience difficulties in emotional regulation and social interaction, indicating the need for appropriate learning strategies. Objective: This study aimed to examine the effect of the storytelling method on the emotional intelligence of children aged 4–5 years at PAUD Taruna Elim. Method: A quantitative study employing a quasi-experimental one-group pretest–posttest design was conducted involving 20 children selected through total sampling. Data were collected using structured observation instruments and analyzed using descriptive statistics and simple linear regression with SPSS. Results: The findings indicated that the storytelling method was positively associated with children's emotional intelligence; however, the relationship was not statistically significant (p = 0.146 > 0.05). The coefficient of determination (R² = 0.114) showed that the storytelling method explained 11.4% of the variance in children's emotional intelligence, while 88.6% was influenced by other internal and external factors beyond the scope of this study. Novelty: This study provides empirical evidence regarding the implementation of storytelling in an authentic early childhood classroom while highlighting the limited contribution of classroom storytelling alone to children's emotional intelligence. Conclusion: Storytelling can support emotional learning experiences, but its effectiveness should be strengthened through interactive classroom activities and continuous collaboration between teachers and parents.